Dr. David Kenneth Rycroft, 7 December 1924 - 8 August 1997 - Kubik, Gerhard (International Library of African Music, 1999)
The shocking news reached me on a bright September 1997 morning, just as we were struggling to get our suitcases through the door of our hostel at Columbia College, Center for Black Music Research, Chicago where we had had a delightful two-month period of work. Our good friend Johann Buis had arrived to take us to O'Hare airport for the flight to Europe, with a letter in his hand. The promising letter came from GROVE, London. It was by Stanley Sadie, and dated 1 September 1997. My vision blurred when I read these sentences: "I expect you heard the sad news of David Rycroft's death. This is very sad, and will make it more difficult for us to have the ideal coverage of South Africa that we had been aiming at.”
Keywords: African Music